PERMAINAN TRADISIONAL MAKEBO-KEBOAN SEBAGAI WAHANA TRANSFORMASI NILAI-NILAI KARAKTER BANGSA DI DESA ULAKAN KECAMATAN MANGGIS KABUPATEN KARANGASEM - I Nengah Karsana; Pradna Lagatama (Sekolah Tinggi Agama Hindu Negeri Mpu Kuturan Singaraja, 2019)
The development of science and technology, and the changing times are one of the reasons why moral degradation occurs. This is caused by the unpreparedness of individuals to accept various changes and the completion of these developments. On the other hand, Indonesia as a country rich in culture, which is full of positive values ??that can help people avoid non-moral actions. Bali as part of the Unitary State of the Republic of Indonesia, is one of the regions that is rich in culture but also faced with the problem of moral degradation. Apparently there is a problem where some cultural products are not able to bring the community away from non-moral activities due to the bias of the meaning of values ??to develop national character, as the main capital that creates superior individuals. For this reason, an analysis of cultural outcomes consisting of the traditional game of macebo-keboan was developed as a medium for national character education, offered based on local cultural values, but still in accordance with the national character and virtue values ??in the global community.Keywords : Traditional Games, Mekebo-keboan, Character Education